2016
DOI: 10.1063/1.4961406
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of VO2 films at the phase transition: Influence of substrate and electronic correlations

Abstract: Thin films of VO2 on different substrates, Al2O3 and SiO2/Si, have been prepared and characterized from room temperature up to 360 K. From the band structure in the rutile metallic phase and in the monoclinic insulating phase the optical properties are calculated and compared with reflection measurements as a function of temperatures. Various interband transitions can be assigned and compared with previous speculations. We extract the parameters of the metallic charge carriers that evolve upon crossing the ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 53 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…With this double process M 1 becomes an insulator (semi-conductor) if δE is large enough so that the bottom energy of the π * band is higher than the upper energy of the d B // band, as shown in Figure 12b. δE measured at ≈ + 0.68 eV at ambient pressure [107,108] supports this scenario. Note that in the opposite situation of negative δE, M 1 should remain metallic.…”
Section: Model Of Goodenough Of the Mitsupporting
confidence: 62%
“…With this double process M 1 becomes an insulator (semi-conductor) if δE is large enough so that the bottom energy of the π * band is higher than the upper energy of the d B // band, as shown in Figure 12b. δE measured at ≈ + 0.68 eV at ambient pressure [107,108] supports this scenario. Note that in the opposite situation of negative δE, M 1 should remain metallic.…”
Section: Model Of Goodenough Of the Mitsupporting
confidence: 62%
“…Typical broadband bowtie antennas have input impedances with a constant real part (typically of the order of tens of ohms depending on both substrate and geometry) and a small imaginary part over the frequency band of interest. On the other hand, the VO 2 switch impedance is dominated by carrier dynamics in VO 2 , which is approximately the same as in DC transport since the collision frequency is of the order of tens of terahertz 27 28 29 , as confirmed by direct measurements of the THz conductivity showing negligible imaginary part and a real part with low dependence on frequency 30 . Hence, the VO 2 switch can be considered as resistive, i.e.…”
Section: Resultsmentioning
confidence: 57%
“…The constants 0 and ∆ D have been extracted from various experimental data presented in the literature in a way that matches the observed values of D in the dielectric and metallic phase [4,14,[27][28][29]. We have found that 0 can take values between 0.02 (or even lower) to 0.1 while the extracted ∆ D varies between 25 − 80.…”
Section: Photonic Crystal With Phase Changing Defectsmentioning
confidence: 66%